2008
DOI: 10.5194/acp-8-471-2008
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tropospheric wave forcing and tropical lower stratospheric water vapor

Abstract: Abstract. Using water vapor data from HALOE and SAGE II, an anti-correlation between planetary wave driving (here expressed by the mid-latitude eddy heat flux at 50 hPa added from both hemispheres) and tropical lower stratospheric (TLS) water vapor has been obtained. This appears to be a manifestation of the inter-annual variability of the BrewerDobson (BD) circulation strength (the driving of which is generally measured in terms of the mid-latitude eddy heat flux), and hence amount of water vapor entering the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…1 is still present, implying that according to this analysis it is neither a related feature of seasonal or QBO behaviour. This feature may be related to possible anomalous atmospheric dynamics in the Southern Hemisphere, such as the Antarctic ozone hole split in 2002 (Manney et al, 2005;Charlton et al, 2005) and/or changes in tropical upwelling due to enhanced wave driving in (Dhomse et al, 2008. The tropics bin from 20 • S-20 • N shows a more negative trend of 5.8 % decade −1 since 1997 compared to the mid-latitudes.…”
Section: Hclmentioning
confidence: 97%
“…1 is still present, implying that according to this analysis it is neither a related feature of seasonal or QBO behaviour. This feature may be related to possible anomalous atmospheric dynamics in the Southern Hemisphere, such as the Antarctic ozone hole split in 2002 (Manney et al, 2005;Charlton et al, 2005) and/or changes in tropical upwelling due to enhanced wave driving in (Dhomse et al, 2008. The tropics bin from 20 • S-20 • N shows a more negative trend of 5.8 % decade −1 since 1997 compared to the mid-latitudes.…”
Section: Hclmentioning
confidence: 97%
“…This increase of the mean tropical upwelling is consistent with a higher, colder and drier tropical tropopause leading to a decrease of water vapour in the lower stratosphere (Randel, 2010, Plate 6). Dhomse et al (2008) had also related the sudden decrease in lower stratospheric water vapour after 2001 with a sudden rise in the strength of the BDC. Those authors used the 50 hPa eddy heat flux averaged from 45 • to 75 • and added from both hemispheres to represent the strength of the BDC.…”
Section: Tropical Upwelling Versus Water Vapourmentioning
confidence: 99%
“…Understanding the observed SWV variations and determining the factors that control such variations have become subjects of great interest in recent years (Holton and Gettelman 2001;Rosenlof et al 2001;Randel et al 2006;Dhomse et al 2008;Wang et al 2014Wang et al , 2015. Observations have shown that SWV increased between 1981 and 2000, began to decrease after 2000, before increasing again after 2005 (Oltmans et al 2000;Hurst et al 2011).…”
Section: Introductionmentioning
confidence: 99%